Rendering Beyond_words in Transitioning to Motherhood Through Visual and Dramatic Arts - Scotti, Victoria; Gerber, Nancy (Voices: A World Forum for Music Therapy, 2017)
The purpose of this doctoral dissertation research study was to use arts-based research methods to explore the beyond_words phenomena of first-time mothers who were in the process of transitioning to motherhood. The multidimensional embodied, emotional, and sensory experiences that accompany new motherhood can be overwhelming, be difficult to articulate verbally, and impact the perceptions of the new mother’s relationship to herself and her child (Crossley, 2009; Lintott & Sander-Staudt, 2011; Prinds et al., 2014). In order to honor and capture the emergent, vital, and multi-dimensional nature of beyond_words in transitioning to motherhood, in this study, arts-based research methods were used to explore and represent these phenomena, otherwise inexpressible in words. The arts-based results are presented as five portrait syntheses and a final synthesis play in four acts that bring to life and invite the viewer to live the mothers’ beyond_words experiences, while simultaneously positioning them within the wider context of current medical and health sciences research perspectives. The final synthesis, which is the featured dramatic play, aspires to give voice and aesthetic power to these mothers’ beyond_words transitioning to motherhood experiences. In the philosophical tradition of ABR (Leavy, 2009, 2015), this study marries the rigor of research with the aesthetic power of the visual and dramatic arts challenging existing assumptions, beliefs, and cultural stereotypes about motherhood and disseminating the results to relevant stakeholders.